Organic contaminants in human breast milk identified by non-targeted analysis. (January 2020) - Tran, Cuong D.; Dodder, Nathan G.; Quintana, Penelope J.E.; Watanabe, Kayo; Kim, Jae H.; Hovell, Melbourne F.; Chambers, Christina D.; Hoh, Eunha
Abstract: Understanding the health implications of human exposure to mixtures of chemical contaminants is aided by analytical methods that can screen for a broad range of both expected and unexpected compounds. We performed a proof-of-concept analysis combining human breast milk, a biomonitoring matrix for determining contaminant exposure to mothers and infants, with a non-targeted method based on comprehensive two-dimensional gas chromatography coupled to time-of-flight mass spectrometry (GC×GC/TOF-MS). A total of 172 presumably anthropogenic halogenated compounds and non-halogenated cyclic and aromatic compounds were tentatively identified in breast milk from San Diego, California through mass spectral database searches. Forty of the compounds were prioritized for confirmation based on halogenation or 100% frequency of detection, and the identities of 30 were verified using authentic standards. Thirty-four (85%) of the prioritized contaminants are not typically monitored in breast milk surveys, and 31 (77%) are regulated in at least one market worldwide, indicating breast milk may be a useful biomonitoring matrix for non-targeted analysis and the assessment of human exposure to future emerging or undiscovered contaminants. Graphical abstract: The picture was taken by Nathan Dodder. Image 1 Highlights: Breast milk as a useful biomonitoring matrix for non-targeted analysis. Successful screening, prioritization, and identification via nontargeted analysis. 172 halogenated and non-halogenated cyclic and aromatic compounds identified in breast milk by non-targeted analysis. 85% of 40 prioritized contaminants are not typically monitored in breast milk surveys. Among the highly identified compounds through mass spectral similarity, 94% verification success rate achieved.